(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The work is devoted to investigations of radiation intensity (insolation) of solar station, placed in Arnasay Region. It has been shown that the size of the insulation depends on the angle of incidence of rays incident on a particular surface and the intensity of solar radiation. The intensity of solar radiation on a surface perpendicular to the sun’s rays is denoted by the letter S, and the intensity of the sun’s radiation on the horizontal surface at the Zenith.